DONALD TRUMP’S POLITICAL AND RHETORICAL STRATEGIES IN THE 2024 UNITED STATES PRESIDENTIAL CAMPAIGN DEBATE: A CRITICAL DISCOURSE AND POPULIST RHETORIC ANALYSIS: Strategi Politik dan Retoris Donald Trump dalam Debat Kampanye Pemilihan Presiden Amerika Serikat 2024: Analisis Wacana Kritis dan Retorika Populis - Yopie A. T. Pangemanan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study examines the political and rhetorical strategies employed by Donald Trump during the 2024 United States presidential debate, focusing on five key tactics: polarization, demonization of opponents, emotional nationalism, anti-institution rhetoric, and personalization of leadership. Utilizing a qualitative approach with critical discourse analysis and rhetorical analysis, the research analyzes the complete transcript of the debate to identify how these strategies construct a populist narrative aimed at mobilizing voter loyalty, delegitimizing political adversaries, and positioning Trump as the sole solution to national crises. The findings reveal that Trump’s communication style is not only content-driven but also performative and symbolic, employing emotionally charged language and stark dichotomies to strengthen collective identity among supporters. Polarization is evident in his framing of “us versus them,” creating clear boundaries between patriotic citizens and perceived threats such as immigrants and political elites. Demonization tactics involve hyperbolic language portraying opponents as existential dangers, effectively generating fear and anger. Emotional nationalism is invoked through nostalgic references to America’s past greatness, reinforcing group cohesion and hope for restoration. Anti-institution rhetoric undermines public trust in media, government, and electoral systems, while personalization of leadership elevates Trump as an indispensable, charismatic figure. While these strategies prove effective in political mobilization, they also raise concerns about increased social fragmentation, erosion of democratic norms, and challenges to institutional legitimacy. This study contributes to the literature on political communication by providing a comprehensive, critical examination of contemporary populist rhetoric within a digital media environment. The results offer valuable insights for scholars, policymakers, and practitioners interested in the dynamics of political discourse and its implications for democratic processes.